CONVERGING AND DIVERGENT LINKS ABOUT OCTOPUS AND HUMAN INTELLIGENCE AND COGNITION - Antônio de Freitas Lüders, Carlo; Eraldo Belarmino Farias, José (Journal of Interdisciplinary Debates, 2022)
Scientific research encompasses cognitive and intellectual issues of cephalopods, specifically octopuses, concerning humans. These links can be both about similarities and differences, which in turn help to demystify this curious and idealized animal that is the octopus. The article aims to clarify possible relationships between these two beings and to prove the opposite about several neural characteristics considered exclusive to vertebrate animals. The study was developed through the method of bibliographic and documentary research, with an emphasis on the use of qualitative analysis.